PENGARUH PENERAPAN MEDIA PEMBELAJARAN PAPAN BUDAYA LOKAL (PBL) TERHADAP HASIL BELAJAR MURID PADA MATA PELAJARAN SENI BUDAYA DI SD INPRES BONE KAB.GOWA - Qalbi, Nur; Ashari, Meisar; Roslyn (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nur Qalbi. 2026. The Effect of Implementing the Local Culture Board (PBL) Learning Medium on Student Learning Outcomes in the Cultural Arts Subject at SD Inpres Bone, Gowa Regency. Elementary School Teacher Education Program, Faculty of Teacher Education and Elementary School Teacher Education This study aims to determine the impact of implementing the Local Culture Board (PBL) learning media on student learning outcomes in the Cultural Arts subject for fifth-grade students at SD Inpres Bone, Gowa Regency. The background of this study is the low level of student learning achievement caused by the use of traditional teaching methods that do not actively involve students in the learning process. This study is a quantitative study with a pre-experimental design that applies the One-Group Pretest-Posttest Design. The sample size was 25 students. The measurement tool used was a learning achievement test administered before (pretest) and after (posttest) the implementation of the PBL media. Data analysis methods used descriptive and inferential statistical analysis with a t-test. The results of the study show that the mean pretest score of 33.4 increased to 80.6 on the posttest. Furthermore, the hypothesis test yielded a calculated t-value of 18.047, while the critical t-value at the 0.05 significance level was 2.063, meaning the calculated t-value is greater than the critical t-value (18.047 > 2.063). This indicates that there is a significant effect of the use of the Local Culture Board (PBL) media on student learning outcomes. Based on these results, it can be concluded that the use of the Local Culture Board (PBL) media is effective in improving student learning outcomes in the Cultural Arts subject in Grade 5 at SD Inpres Bone, Gowa Regency. Translated with DeepL.com (free version)